Training manual on vegetable seed systems. Module 4: Seed value chain development: Integrated vegetable seed systems development in ethnic minority communities in Northern Vietnam for enhanced nutrition and income security - Pham Thi, Huong Mai; Nguyen, Thi Tan Loc; Le, Nhu Thinh; Swaans, Kees; Le, Van Thuan; Hoang, Van Thi; Van, Lam Luong; Trinh, Quang Tuan (2024)
Vegetables are a main source of income and nutrition for ethnic minority farmers in Vietnam’s Northern highlands. While value chains for fresh produce and seed markets offer significant opportunities for development—particularly for women and youth—the current smallholder seed systems suffer from multiple problems. Such problems include inadequate access to quality seeds, lack of guaranteed product quality, poor storage and treatment practices, and limited smallholder participation in seed value chains. This training manual based on the project’s experiences and lessons learned is designed to assist facilitators in designing and customizing their own training sessions on seed system related topics. The manual is made up of four modules. This is Module 4: Seed Value Chain Development, that presents a discussion on the organisation of seed value chains and provides self-assessment tools and guidance for farmer groups interested in producing and selling seeds as a business.